PATHOGENETIC BASIS OF TREATMENT IN RECURRENT VARICOCELE (International journal of medical sciences, 2026)
Recurrent varicocele is a common urological disorder that negatively affects male reproductive function and fertility. It develops after previous surgical or minimally invasive interventions, resulting in persistent venous reflux, testicular hypoxia, and oxidative stress, which collectively impair spermatogenesis. Accurate diagnosis through clinical examination, Doppler ultrasonography, and advanced imaging modalities is essential for identifying recurrence and guiding treatment. Management strategies should be based on pathogenetic principles, incorporating microsurgical, endovascular, and conservative approaches tailored to patient anatomy, prior interventions, and fertility goals. Surgical precision, prevention of venous stasis, and postoperative monitoring are crucial for reducing recurrence rates. Adjunctive pharmacological therapies, including antioxidants and lifestyle modifications, support testicular function and enhance reproductive outcomes. This review highlights the pathophysiological mechanisms underlying recurrence, evaluates current treatment options, and emphasizes evidence-based strategies to preserve testicular function and improve quality of life in affected men.